Accessibility for pedestrians under heat stress: the example of Heidelberg, Germany - Huber, Johannes; Ludwig, Christina; Foshag, Kathrin; Kolaxidis, Nikolaos; Zipf, Alexander; Lautenbach, Sven (AGILE: GIScience series, 2025)
Anthropogenic climate change, combined with specific modifications of the urban climate, is expected to lead to an increase in the intensity, duration, and frequency of heat waves in urban areas. Prolonged heat stress - as expected due to these changes - has serious health consequences for vulnerable urban population groups. This study examines the effects of heat stress on the accessibility of essential services in Heidelberg, Germany. The concept of isochrones was extended to include heat stress factors and applied to the study area, the city of Heidelberg in Germany. The analysis was based on a heat-sensitive routing approach that uses OpenStreetMap data together with a digital surface model that was used to model solar exposure. Results showed that under moderate heat stress conditions, accessibility to essential services (transportation, healthcare, retail and social services) was largely maintained, while under high heat stress conditions, a significant portion of the population was excluded from these services. Differences in the affected population can be identified according to both administrative territorial units and building structures. The results provide relevant information for urban planning as they indicate where city inhabitants will face problems to access essential services under heat spells.
Gesehen am 23.06.2025
Proceedings of the 28th AGILE Conference on Geographic Information Science, 10-13 June 2025